Implementasi Pembelajaran Kooperatif Learning Together Sebagai Upaya Meningkatkan Pemahaman Siswa Kelas V pada Materi Huruf Kapital - Huda, Yusuf Khoirul (IIQ An Nur Yogyakarta, 2025)
This study aims to improve students' understanding of capital letters through the implementation of the Learning Together cooperative learning model among fifth-grade students at MI Miftahul Huda Jatisari. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The findings indicated a significant improvement in student understanding, from 37% in the pre-cycle, to 59% in cycle I, and reaching 81% in cycle II. This increase demonstrates the effectiveness of the Learning Together model in building students’ comprehension through group work, active discussion, and engaging learning media. Practically, the study shows that cooperative learning strategies, when combined with reflective practices and technology, can enhance learning outcomes and foster active student engagement. The research contributes to the development of more participatory and meaningful Indonesian language learning strategies at the elementary level.